The role of Diu in the Hindu-Gujarati diaspora in Portugal - Lourenço, I. (2018)
This article introduces the Diu transnational population with ties to Mozambique, Portugal, and the United Kingdom, with the aim of portraying these ties historically, socially, and culturally. Both authors have engaged in long-term ethnographic fieldwork, mostly working together to generate advantages for the study of transnationality and diaspora. Therefore, this article details our view after more than a decade of fieldwork while also conveying the voices of our interlocutors, who better illustrate Diu and its plural dimensions. The article describes the Diu Hindu representations of late Portuguese colonialism in India (until 1961) and explains the plural dimensions of transnationality. On the one hand, we focus on the cultural practices associated with transnationality, paying special attention both to the return to India and to marriages. On the other hand, the article explores the types of migration from Diu to other countries.